Analysis of Impact Deformation of Corrugated and Anisotropic Shells - Gordienko, B.A. (Engineering Transactions, 1976)
The existence of material anisotropy (at E2/E1<1) in the shells subjected to impact loaying lowers the critical time and leads to axi-symmetric forms buckling. The data of experiments performed on the longitudinally corrugated shells connfirm the theoretical results obtained.